Food Contamination Risks in Food Service Establishments in Banjarbaru Using a Risk-Based Sanitation Hygiene Inspection Approach - Isnawati, Isnawati; Rahmawati, Rahmawati; Noraida, Noraida; Indah Hati, Fatmi; Syainah, Ermina (JURNAL KESEHATAN LINGKUNGAN: Jurnal dan Aplikasi Teknik Kesehatan Lingkungan, 2025)
The widespread and large number of Food Management Facilities and the limited number of environmental health officers as supervisors pose a unique challenge to the current inspection system in implementing field supervision. Effective monitoring efforts are essential to ensure food safety at TPP. The research aims to examine how risk-based sanitation and hygiene inspections are applied at the Banjarbaru City TPP. This research method is observational with a cross-sectional approach using the Environmental Health Inspection Instrument. Samples were taken based on five TPP categories: restaurants, catering services, food stalls, DAMIU, and IRTP. A risk-based analysis was conducted based on the cumulative value of food risks, including food profiles and mitigation of these food hazards. Business risks assessed business size and the risk of non-compliance during inspection. The research results show that 60% of TPPs are in the medium-risk category with an inspection frequency of once a year, 20% are in the high-risk category with an inspection frequency of twice a year, and 20% are in the low-risk category with an inspection frequency of once every two years. It is recommended that consistent supervision and periodic monitoring be implemented so that every food management facility can guaranty food safety and quality for consumers, thus protecting public health from hazardous food risks. Regular inspections not only increase consumer confidence but also strengthen businesses' commitment to providing high-quality and safe food.